Analyses and profiling of extract and fractions of neglected weed mimosa pudica Linn. traditionally used in Southeast Asia to treat diabetes - Tunna, T.S.; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Ghafoor, K.; Al-Juhaimi , F.Y.; Uddin, M. S; Hasan, M.; Ferdosh, Sahena (Elsevier, 2015)
Mimosa pudica Linn. var. hispida Bren. (Family: Fabaceae) a neglected weed has been studied for its antidiabetic potential to propose alternative medicinal source against the global threat of diabetes mellitus. This study aimed to investigate in vitro inhibitory activity against diabetic enzymes (i.e. α-amylase & α-glucosidase) and three anti-oxidant assays were conducted to evaluate anti-diabetic potential of M. pudica’s methanol extract (MeOHi) and its sub-fractions (Hexanef, EtOAcf, Acetonef and MeOHf). In depth chemical profiling using GC Q-TOF MS was also performed for the first time for this weed, to assess the probable compounds present in the extract and sub fractions that could be linked to anti-diabetic activity. Results showed the lowest (7.18±0.0005) and highest (158.4±0.0004) IC50 for DPPH assay by MeOHi andMeOHf, respectively. Acetonef andMeOHi showed the highest TPC (60.07±1.066) and TFC (16.97± 1.472), respectively. Three and two fold higher inhibitory activity than the standard acarbose at 1mg/ mL wasmanifested byMeOHi (95.65±0.911) & EtOAcf (51.87±3.106), respectively. Hexanef did not show inhibitory activity against both the enzymes. α-glucosidase results for the extract and sub fractions were found to be significant (p b 0.05). GC Q-TOF MS analysis identified organic acids, quinolones, quinone, phenolic compounds and dodecaborane as major constituents. Presence of highly radical scavenging dodecaborane is being reported for the first time in M. pudica. High TPC and TFC values could be attributed to exert enzyme inhibitory action byM. pudica that can help in the regulation of glucose absorption and consequently glucose homeostasis. Results show that M. pudica can be proposed as an excellent alternative for future antidiabetic implications.